Maturation of early visual processing investigated by a pattern-reversal habituation paradigm is altered in migraine - Oelkers-Ax, Rieke; Parzer, Peter; Resch, Franz; Weisbrod, Matthias (Cephalalgia, 2005)
Evidence for a disturbed maturation of information processing in migraine came recently from evoked and event-related potential studies during childhood. In adult migraineurs, deficient habituation is proposed as principal interictal abnormality and was found inter alia for Visual Evoked Potentials (VEPs). This study investigated response and habituation to pattern-reversal VEPs and its maturation in 102 children with primary headache (migraine with and without aura, tension-type headache) and 79 healthy controls from 6 to 18 years. A reduction of N180 latency from pre- to postpubertal age reflects maturation and was clearly present in controls but lessened in migraineurs. N180 latency was prolonged in migraineurs without aura from 12 years onwards. Habituation did not differ between groups. In conclusion, diminished N180 latency reduction with age in migraineurs gives further evidence that maturation of visual information processing is altered in migraine. Deficient habituation to pattern-reversal VEPs could not be confirmed during childhood migraine.